2020
DOI: 10.1111/ejh.13489
|View full text |Cite
|
Sign up to set email alerts
|

Major central nervous system complications after allogeneic stem cell transplantation: A large retrospective study on 888 consecutive adult patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The incidence of abnormal findings in autopsies is up to 90% (24). A recent Chinese study assessing 196 children (8) found the incidence to be 17%, comparable with our results (and similar to the 14.8% incidence in a recent study on 888 adult allotransplanted patients) (17). The incidence of NCs after HSCT is higher than in children treated with chemotherapy only (10).…”
Section: Neurological Complications 107supporting
confidence: 91%
See 2 more Smart Citations
“…The incidence of abnormal findings in autopsies is up to 90% (24). A recent Chinese study assessing 196 children (8) found the incidence to be 17%, comparable with our results (and similar to the 14.8% incidence in a recent study on 888 adult allotransplanted patients) (17). The incidence of NCs after HSCT is higher than in children treated with chemotherapy only (10).…”
Section: Neurological Complications 107supporting
confidence: 91%
“…GVHD was found to be correlated with NCs (9,12); a recent retrospective analysis revealed statistically significant correlations between noninfectious NCs and GVHD, specifically between PRES or seizures, and acute GVHD, as well as seizures or stroke, and chronic GVHD; but causal relationships could not be established (4). The abovementioned large adult study found increased age as the only significant risk factor (17).…”
Section: Neurological Complications 107mentioning
confidence: 96%
See 1 more Smart Citation
“…Although the presence of CNS dysfunction is essential for the diagnosis of HHV-6 encephalitis, allo-HSCT recipients may develop CNS dysfunction due to many other factors than HHV-6 encephalitis. 32,33 In our study, only 14 out of 41 patients with CNS dysfunction after allo-HSCT were caused by HHV-6 encephalitis. The sensitivity, speci city, PPV, NPV, LR+, and LR-of CNS dysfunction for the diagnosis of HHV-6 encephalitis were 100%, 77.5%, 34.1%, 100.0%, 4.444, and 0.000, respectively (Table 3).…”
Section: Timing Of Hyponatremia Hhv-6 Encephalitismentioning
confidence: 66%
“…1d ). Allo-HSCT recipients may develop CNS dysfunction due to many other factors than HHV-6 encephalitis [ 11 ]. In fact, 27 (65.9%) of 41 patients with CNS dysfunction had other causes than HHV-6 encephalitis in this study.…”
Section: To the Editormentioning
confidence: 99%